Employee’s Wellbeing at Work and Performance in Healthcare Sector—Taking Chinese Healthcare Employees as Research Object - Liu, kelu (2018)
Employee wellbeing has always been an essential section in human resource management practices, as employee's physical and psychological health will impact both individual work performance and organization performance. This study is going to explore the potential sources that may affect employee wellbeing at the workplace, especially in the healthcare sector, and the interplay between employee wellbeing and work performance. Basically, five main domains will be selected—job stress, job burnout, work-life balance, the doctor-patient relationship, and job satisfaction. Detailed discussion will be given about how each of them may influence employee wellbeing, and there will be general comparisons based on realistic examples between western countries and China. It is worth noting that these factors are mutually shaped and can bring positive or negative effects to employee wellbeing according to their conditions. What is more, employee survey has been conducted by online questionnaire among healthcare employees working in regular medical institutions in Yueyang, China. Practical information about the present medical staff's wellbeing can be gained from their responses, which make this study more valuable. Finally, several suggestions will be advised. This study might be helpful to attract the attention of employees themselves, hospital management and society in the significance of employee wellbeing.